MSME Competitive Strategy After Covid-19 in Pekalongan City (Case Study of Agifa Batik) - Reza Amalia; Ria Mardiana; Andi Reni (Program Studi Akuntansi Universitas Kristen Indonesia Paulus, 2023)
Batik is a characteristic of Indonesian culture that has great economic potential for Indonesia. However, the large number of Batik business actors in Pekalongan City shows competition. To be able to survive and thrive, proper analysis is needed to find out the right strategy to face competitors. The determination of the strategy of Agifa Batik MSMEs using SWOT Analysis which is classified with IFE and EFE matrices to find out the internal factor score is 2.7 and the external factor is 2.4 which means that the position of Agifa Batik MSMEs is in a developing position. From the SWOT analysis, Agifa Batik MSMEs can take advantage of their strengths and opportunities into a stronger strategy and existing weaknesses and threats can be overcome by looking at the opportunities they have.